Circular RNA expression profile of Alzheimer's disease and its clinical significance as biomarkers for the disease risk and progression. (June 2020) - Li, Yuanlong; Fan, Hua; Sun, Jun; Ni, Ming; Zhang, Lei; Chen, Ci; Hong, Xuejiao; Fang, Fengqin; Zhang, Wei; Ma, Peizhi
Abstract: Objective: To investigate circular RNA (circRNA) expression profile via microarray, and further assess the potential of candidate circRNAs as biomarkers in Alzheimer's disease (AD). Methods: CircRNA expression profile in cerebrospinal fluid from 8 AD patients and 8 control (Ctrl) subjects was assessed by microarray. Subsequently, 10 candidate circRNAs from microarray were validated by reverse transcription quantitative polymerase chain reaction (RT-qPCR) in cerebrospinal fluid from 80 AD patients and 40 Ctrl subjects. Results: By microarray, 112 circRNAs were upregulated and 51 circRNAs were downregulated in AD patients compared with Ctrl subjects, and these circRNAs were enriched in AD related pathways such as neurotrophin signaling pathway, natural killer cell mediated cytotoxicity and cholinergic synapse. By RT-qPCR, circ-LPAR1, circ-AXL and circ-GPHN were increased, whereas circ-PCCA, circ-HAUS4, circ-KIF18B and circ-TTC39C were decreased in AD patients compared with Ctrl subjects, and these circRNAs were disclosed to predict AD risk by receiver operating characteristics curve analysis. Further forward-stepwise multivariate logistic regression revealed that circ-AXL, circ-GPHN, circ-ITPR3, circ-PCCA and cic-TTC39C were independent predictive factors for AD risk. Besides, in AD patients, circ-AXL and circ-GPHN negatively correlated, while circ-PCCA and circ-HAUS4 positively correlated with mini–mental state examination score; Circ-AXL negatively correlated, while circ-PCCA, circ-HAUS4 and circ-KIF18B positively correlated with Aβ42 ; Circ-AXL and circ-GPHN positively correlated, whereas circ-HAUS4 negatively correlated with t-tau; Circ-AXL positively correlated with p-tau. Conclusion: Our study provides an overview of circRNA expression profile in AD, and identifies that circ-AXL, circ-GPHN and circ-PCCA hold clinical implications for guiding disease management in AD patients.